Pengembangan Video Pembelajaran Matematika Berbasis Aplikasi Geogebra untuk Meningkatkan Pemahaman Konsep Siswa Kelas VIII SMP Negeri 1 Belitang Hilir Dalam Materi Persamaan Garis Lurus - Firanti, Firanti; Alhadad, Syarifah Fadillah; Muchtadi, Muchtadi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop learning media in the form of a GeoGebra application-based math learning video to improve the understanding of the concepts of students in grade VIII of SMP Negeri 1 Belitang Hilir. This Research is a Development Research (R&D) using the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects in the study consisted of material and media experts (as validators), as well as students and teachers (as product trial subjects). Data collection techniques were conducted through indirect communication, using instruments in the form of expert validation sheets, teacher response questionnaires, and student response questionnaires. The results of validation by material experts showed a validity level of 91.9% and by media experts of 93.84%, both of which were included in the very valid category. The teacher response questionnaire showed a practicality level of 97.64%, while the student response questionnaire was 90.13%, both included in the very practical category. In addition, the posttest results showed the effectiveness level of the learning media of 77.28% which was included in the effective category. Thus, the GeoGebra-based learning video media developed is considered valid, practical, and effective for use in learning mathematics.